Inventors among the "impoverished sophisticate" - Thor Berger; Erik Prawitz (Research Institute of Industrial Economics (IFN), 2023)
This paper examines the identity and origins of Swedish inventors prior to World War I drawing on the universe of patent records linked to census data. We document that the rise of innovation during Sweden's industrialization can largely be attributed to a small industrial elite belonging to the upper-tail of the economic, educational, and social status distribution. Analyzing children's opportunities to become an inventor, we show that inventors were disproportionately drawn from privileged family backgrounds. However, among the middle- and working-class children that managed to overcome the barriers to entry, innovation was a path to upward mobility.
Keywords: O31; J62; I25; 330; Innovation; inventors; intergenerational mobility